The use of psychoactive substances among Ukrainian youth (based on the materials of the international project "Mental Health and Risky Behaviour of Adolescents") = Stosowanie substancji psychoaktywnych przez ukraińską młodzież (na podstawie materiałów międzynarodowego projektu "Zdrowie psychiczne i ryzykowne zachowania młodzieży") - Mirchuk, Iryna; Zelena, Oksana (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article focuses on the use of alcohol and other psychoactive substances (PAS) among young people (using the example of ninth-grade students in the cities of Lviv, Drohobych, and the Drohobych Raion). The paper reports on the results of the project "Mental Health and Risky Behaviour of Adolescents", conducted in 2020 by a joint team of Ukrainian and Polish researchers (from Ivan Franko Drohobych State Pedagogical University, Lviv Polytechnic National University, as well as the State Agency for the Prevention of Alcohol Related Problems (PARPA) and the Institute of Neurology and Psychiatry (Warsaw), using the methodology of the Mokotow Study.
Keywords: youth; psychoactive substances; alcohol; drugs; cigarettes; młodzież; substancje psychoaktywne; alkohol; narkotyki; papierosy